2019
DOI: 10.1186/s12879-019-3800-2
|View full text |Cite
|
Sign up to set email alerts
|

Is Interleukin-6 a better predictor of successful antibiotic therapy than procalcitonin and C-reactive protein? A single center study in critically ill adults

Abstract: Background The aim of this study was to evaluate whether Interleukin-6 (IL-6) could be a faster indicator of treatment success in adults with severe sepsis and septic shock compared to procalcitonin (PCT) and C-reactive protein (CRP). Methods Data from adult patients with severe sepsis and septic shock managed at the medical intensive care unit (ICU) of the University Hospital Leipzig between September 2009 and January 2012 were analyzed retrospectively. Values for CRP,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(64 citation statements)
references
References 33 publications
2
60
0
2
Order By: Relevance
“…Measurement of the immune status, such as PD-1/programmed death ligand 1 (PD-L1) expression on T cells and dendritic cells, lymphocyte count, HLA-DR expression on monocytes, immunoglobulin levels and inflammatory markers (e.g. CRP, IL-6 or PCT) are potential diagnostic biomarkers to be considered [105,118,119]. Low HLA-DR expression, in particular, may correlate with low lymphocyte counts in the differential blood count and lymphocyte count is also readily available in most hospitals.…”
Section: Patients With Immunosuppression Clinical Phenotypementioning
confidence: 99%
“…Measurement of the immune status, such as PD-1/programmed death ligand 1 (PD-L1) expression on T cells and dendritic cells, lymphocyte count, HLA-DR expression on monocytes, immunoglobulin levels and inflammatory markers (e.g. CRP, IL-6 or PCT) are potential diagnostic biomarkers to be considered [105,118,119]. Low HLA-DR expression, in particular, may correlate with low lymphocyte counts in the differential blood count and lymphocyte count is also readily available in most hospitals.…”
Section: Patients With Immunosuppression Clinical Phenotypementioning
confidence: 99%
“…The blood IL-6 levels are elevated in patients with sepsis and septic shock [35,36], correlate with disease severity [35][36][37], and possibly predict unfavorable outcome [36]. Moreover, IL-6 could be a faster indicator of treatment success in adults with severe sepsis and septic shock compared to PCT and CRP [37]; however, some studies found no additive effect for IL-6 in the diagnosis of the severe infection in critically ill patients [38]. In a recently published systematic review regarding biomarkers of sepsis, Pierrakos et al indicated that IL-6 in comparison with PCT and/or CRP for sepsis diagnosis provided conflicting findings and that so far IL-6 was not evaluated for prognostic value in large clinical studies [39].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, as IL‐6 and sIL‐6Rα are acute reactants, their plasma levels in non‐disease states are very low, but they increase rapidly and substantially in conditions of acute inflammation, such as myocardial infarction (MI), severe infections, and trauma . MI and trauma induce endothelial injury and the exposure of the subendothelial matrix at the site of vascular injury.…”
Section: Discussionmentioning
confidence: 99%